Itinerários da produção e consumo de artesanato em comunidades tradicionais de Penedo-AL - Lima, Fabiana de Oliveira; dos Santos Militão, Daniele; da Silva Santos, Ana Paula (RITUR - Revista Iberoamericana de Turismo, 2021)
Consumption is configured as a complex field of symbolic constructions. In turn, the consumption of cultural goods has proven to be a robust territory for understanding cultural relations, as well as the dynamics of their transformations and adaptations. In this sense, we developed a study in the city of Penedo-AL that has outstanding intangible cultural riches, such as its production of handicrafts, common and traditional, and we present it as a research report. Our objective was to verify the consumption of cultural goods produced in traditional communities and their implication in cultural tourism and leisure activities. With an anthropological understanding of consumption in mind, we started from the ethnographic method and developed a field work, constituting a qualitative research, through semi-structured interviews with artisans, consumers, presidents of associations, merchants and public authorities. In this way, we understand that the symbolic values attributed by the artisans reinforce social relations, despite the adaptations coming from consumers. The associations presented themselves as spaces that promote an effective difference for artisans and their productions. Social media and its display features have been an important showcase, especially during the pandemic. Finally, we highlight the importance of reflecting on how the process of constructing the symbolic value of handicrafts has contributed to its transformations, influenced by visitors or representations of cultural consumption.